sakura
1 tháng 4 2017 lúc 10:18

\(\frac{4}{7}+x\times2=\frac{5}{3}\)

           \(x\times2=\frac{5}{3}-\frac{4}{7}\)

           \(x\times2=\frac{23}{21}\)

                    \(x=\frac{23}{21}:2\) 

                     \(x=\frac{23}{42}\)

Bình luận (0)
✓ ℍɠŞ_ŦƦùM $₦G ✓
1 tháng 4 2017 lúc 10:16

\(\frac{4}{7}+x\times2=\frac{5}{3}\)

          \(x\times2=\frac{5}{3}-\frac{4}{7}\)

           \(x\times2=\frac{23}{21}\)

                   \(x=\frac{23}{21}:2\)

                   \(x=\frac{23}{42}\)

Vậy x = 23/42

Bình luận (0)
Khôi Nguyên Hacker Man
1 tháng 4 2017 lúc 10:16

x*2=5/3-4/7

x*2=23/21

x   =23/21:2

x   =23/42

Bình luận (0)

Các câu hỏi tương tự

Khoá học trên OLM của Đại học Sư phạm HN

Loading...

Khoá học trên OLM của Đại học Sư phạm HN